Entre estrofes e saberes: uma sequência didática com a canção “Feira santarena” no ensino médio - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This paper is an experience report resulting from a teaching sequence carried out in a public school in the city of Santarém-PA. The topic addressed involves the use of textual genres and the study of the lyrics of a song as a learning object. The pedagogical experience was carried out in high school through work with the textual genre "song" using the song Feira Santarena, composed by Emir Bemerguy (1933) and sung by the Maestro Wilson Fonseca Choir (1967). The teaching sequence was applied during the discipline "Supervised Internship in Portuguese Language IV" (offered by the Bachelor's Degree in Literature at the Federal University of Western Pará) at the Rodrigues dos Santos State High School, and aimed to provide students with the opportunity to analyze and interpret linguistic and cultural elements present in the lyrics of the song from their region. The approach was based on the importance of textual genres for the development of reading and writing skills, combining pedagogical practice with the students' cultural and regional repertoire. In addition to being an artistic element, songs carry linguistic and sociocultural traits that reflect the identity of a community. Thus, the study sought to demonstrate how the exploration of textual elements, such as stanzas, verses, rhythm and regional expressions, can contribute to meaningful learning of the Portuguese language, promoting greater student engagement and the appreciation of the culture of Santarém.
Keywords: Sequência didática; Gêneros textuais; Canção; CNPQ:: LINGÜÍSTICA, LETRAS E ARTE